PENGARUH KOMPETENSI KOMITE AUDIT, AKTIVITAS KOMITE AUDIT DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA - Metta Kusumaningtyas; Dessy Noor Farida (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2015)
The objective of this study is to analyze the influence of audit committee and institutional ownership on earnings management. The characteristics that used to measure the effectiveness of the audit committee competence,and audit committee activity. Institutional ownership is measured by the number of proportion of shares held by institutional shareholders divided by the number of shares issued. Earnings management in this study weremeasured by using the value of discretionary accrual. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2007-2012. Based on purposive sampling method, the number of samples in this study of 300 samples. Testing the hypothesis using multiple regression analysis. The results of hypothesis testing indicate that audit committee competence and audit committee activity had a significant negative effect on earnings management. Instead institutional ownership had not influence on earnings management.